2021
DOI: 10.5603/pjnns.a2020.0097
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil-to-lymphocyte ratio (NLR) at boundaries of Progressive Supranuclear Palsy Syndrome (PSPS) and Corticobasal Syndrome (CBS)

Abstract: Aim of the study. To examine possible features of neuroinflammation in progressive supranuclear palsy -Richardson syndrome and corticobasal syndrome (CBS).Clinical rationale for the study. Neutrophil-to-lymphocyte ratio (NLR) is a parameter reflecting inflammation used in numerous branches of medicine. The search for pathogenesis of the diseases partly related to inflammatory processes confirms the need to obtain possible factors which could be relatively easily verified. NLR is a benchmark routinely evaluated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 16 publications
1
21
0
Order By: Relevance
“…This study highlights the need to search for accessible tools facilitating the management and diagnosis of Parkinson's Disease and Multiple System Atrophy. To the best of our knowledge, this is the first paper evaluating PLR in the context of atypical parkinsonian syndrome; this parameter should be assessed in patients with atypical parkinsonian syndromes, as previously published studies have shown interesting results in the context of peripheral inflammation markers [56].…”
Section: Clinical Implications/future Directionsmentioning
confidence: 91%
“…This study highlights the need to search for accessible tools facilitating the management and diagnosis of Parkinson's Disease and Multiple System Atrophy. To the best of our knowledge, this is the first paper evaluating PLR in the context of atypical parkinsonian syndrome; this parameter should be assessed in patients with atypical parkinsonian syndromes, as previously published studies have shown interesting results in the context of peripheral inflammation markers [56].…”
Section: Clinical Implications/future Directionsmentioning
confidence: 91%
“…Moreover, it gives new insight that could support the research of an early diagnosis of AD. Future studies will investigate the relationship between non-specific blood analytes and the progression of other forms of dementia (e.g., Fronto-temporal dementia, Lewy body dementia) as well as other neurodegenerative diseases often associated with dementia symptoms (e.g., Parkinson disease [ 76 ]). Our methodological approach could highlight similarities and differences with AD, providing not only a tool for a more objective prognosis of such different forms of dementia but also a powerful approach for a differential diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Alzheimer’s disease (AD) and Parkinson’s disease (PD) are two neurodegenerative disorders reported to be caused by prolonged inflammation in patients infected by SARS-CoV-2 as a possible postinfectious manifestation. Inflammatory processes are also involved in other neurodegenerative disorders such as progressive supranuclear palsy syndrome (PSPS) [ 64 ], corticobasal syndrome (CBS) [ 64 ], and multiple system atrophy-parkinsonian type (MSA-P) [ 65 ]. COVID-19 has been reported to affect the international classification of functioning, disability, and health functioning in patients with MSA [ 66 ].…”
Section: Impact Of Covid-19 On Neuropsychiatric Disordersmentioning
confidence: 99%